Spirituality: What is Its Role in Pain Medicine?. Issue 1 (26th August 2014) - Siddall, Philip J.; Lovell, Melanie; MacLeod, Rod
Abstract Background For many years, spirituality has been regarded as an integral aspect of patient care in fields closely allied to pain medicine such as palliative and supportive care. Despite this, it has received relatively little attention within the field of pain medicine itself. Reasons for this may include a lack of understanding of what spirituality means, doubtfulness of its relevance, an uncertainty about how it may be addressed, or a lack of awareness of how addressing spirituality may be of benefit. Methods A review of the literature was conducted to determine the changing conceptual frameworks that have been applied to pain medicine, the emergence of the biopsychospiritual approach and what that means as well as evidence for the benefits of incorporation of this approach for the management of pain. Results Although the concept of spirituality is broad, there is now greater consensus on what is meant by this term. Many authors and consensus panels have explored the concept and formulated a conceptual framework and an approach that is inclusive, accessible, relevant, and applicable to people with a wide range of health conditions. In addition, there is accumulating evidence that interventions that address the issue of spirituality have benefits for physical and emotional health. Conclusions Given the firm place that spirituality now holds within other fields and the mounting evidence for its relevance and benefit for people with pain, there is increasing evidence to support the inclusion of spiritual factors as an important component in the assessment and treatment of pain.